A Study on Antimicrobial Evaluation of Different Generic and Branded Tablet of Ciprofloxacin HCl Marketed in Wardha District - Dighade, Sachin J.; Chore, Shramika A; Gaurkar, Sunit D (Journal of Pharmacy Practice and Community Medicine)
Bacterial infection is responsible for various activity including respiratory, urinary tract, gastrointestinal and abdominal infections. Ciprofloxacin HCl, a second-generation fluroquinolone antibiotic that can treat a number of bacterial infections. The aim of this work was to evaluate antimicrobial activity of different generic and branded drug formulation marketed in Wardha district. i.e. Cifran and Zoxan. All the formulations obtained from the market were in compliance with the control samples in respect of Preformulation study, Disintegration, in vitro drug release, and antimicrobial potential. Thus, the antimicrobial activity of marketed and control sample was also same shows satisfactory results against Staphylococcus aureus as compare to Escherichia coli, but Staphylococcus aureus was shows better microbiological assay response as compare to E. coli.
Keywords: Ciprofloxacin HCl; Preliminary; Branded and Generic drug; Cifran; Zoxan; Antimicrobial potential etc